Comparison of the MicroRNA Expression Profiles of Male and Female Avian Primordial Germ Cell Lines - Bence Lázár; Mahek Anand; Roland Tóth; Eszter Patakiné Várkonyi; Krisztina Liptói; Elen Gócza (Stem Cells International)
Primordial germ cells (PGCs) are the precursors of adult germ cells, and among the embryonic stem-like cells in the bird embryo, only they can transmit the genetic information to the next generation. Despite the wide range of applications, very little is known about the mechanism that governs primordial germ cell self-renewal and differentiation. As a first step, we compared 12 newly established chicken PGC lines derived from two different chicken breeds, performing CCK-8 proliferation assay. All of the lines were derived from individual embryos. A significant difference was found among the lines. As microRNAs have been proved to play a key role in the maintenance of pluripotency and the cell cycle regulation of stem cells, we continued with a complex miRNA analysis. We could discover miRNAs expressing differently in PGC lines with high proliferation rate, compared to PGC lines with low proliferation rate. We found that gga-miR-2127 expresses differently in female and male cell lines. The microarray analysis also revealed high expression level of the gga-miR-302b-3p strand (member of the miR-302/367 cluster) in slowly proliferating PGC lines compared to the gga-miR-302b-5p strand. We confirmed that the inhibition of miR-302b-5p significantly increases the doubling time of the examined PGC lines. In conclusion, we found that gga-miR-181-5p, gga-miR-2127, and members of the gga-miR-302/367 cluster have a dominant role in the regulation of avian primordial germ cell proliferation.